Towards An Islamic Critique of Anthropological Evolutionism - A. Muhammad Ma’ruf (International Institute of Islamic Thought, 1986)
I. THE BIOLOGY-CULTURE CONNECTION IN THE HISTORY OF ANTHROPOLOGICAL THOUGHT The story of modem anthropology is a story of the Euro-American attempt to discover the other than Euro-American human being. Within that story is the story of the intellectual self-discovery of the Euro-American; within that is the story of the discovery of racism; within that is the story of political and ideological pressures on the processes of such discoveries; within that the amazing and wonderful story of the scientific discovery of the worldly nature of the human being - conceptualized generally: across all space and time, all colors and languages; and within that story is a story of the social and natural sciences: of their methods, results, potentialities, and pitfalls. If there is a central theme that runs through all these stories within the story, it is the story of the impact of Darwinian and post-Darwinian biology on the social and human sciences. Modem anthropology is not much more than an evolutionist form of humanism. Evolutionism is to be found in most types of contemporary anthropological studies, as a central position or an implicit assumption. It is clearly axiomatic to thought, analysis, and interpretation in the discipline. As such it is a fundamental issue in the consideration of modem anthropology for inclusion in, and recasting for, Islamic educational purposes. The aim of this presentation is to consider briefly how the impact of Darwin, and of biology after Darwin, on recent anthropological thought may be measured as a step toward developing an Islamic methodology for anthropological research and teaching. Since its publication in 1859 by Charles Darwin (and Alfred Russell), evolutionary theory has been refined and developed by virturally all life science disciplines and a few other disciplines such as anthropology. Anthropdogy is rooted partly in the life sciences and partly in the social sciences. Human evolutionary theory developed by anthropologists has gained wide acceptance in all sectors of the Western scientific establishment. Adherence to, and propagation of, an evolutionist world-view has become a symbol of the liberalist mission of Western science in the face of periodic opposition to it coming from conservative, evangelist, Christian fundamentalists, and politicians who represent them. A few of the anti-evolutionists are also scientists (Williams, 1983). They have given leadership to the most recent form of antievolutionism, called scientific creationism. Within the scientific and educational community their view is at present a minority view; the dominant view being the pro-evolutionary one. Among the Judeo-Christian population at large, in the United States, surveys indicate that about half of the people give credence to the evolutionary view. The others either do not or do not care. An effect of post-Darwinian natural science on social science was to bring human evolution into focus as incorporating psychological, social, and cultural aspects in addition to the biological (see e.g. in Eiseley, 1958; Freeman, 1974; Harris, 1968; Opler, 1964; Reed, 1961; Stocking, 1968). The historical relationship of bio-evolutionary theory to the social sciences in general and specifically to anthropology, is complex. Nowadays it is one of the dependence of the latter on the former. It has been argued, however, that in its formative years, Darwinian evolutionary theory was in fact an application of social science concepts to biology. Darwin himself acknowledged that the Malthusian statement of the principle that human population, when unchecked, increases in geometrical ratio while subsistence increases only in arithmetical ratio, influenced his idea of natural selection. The subsequent acceptance of Mendelian genetics, on which the modem form of evolutionism rests, quickly transformed even the fundamental social science principles of the study of human races and variation. The continuing success of the biological sciences ...